1974
DOI: 10.1128/jb.119.2.410-415.1974
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of the Rate of α-Amylase Synthesis in Bacillus subtilis

Abstract: MATERIALS AND METHODS Bacterial strains. Strains of B. subtilis used in this study were derivatives of strain 168 of Burkholder and xiles (2). Strains 6160 (metB5 purB6 trp-160 amyEm+ amyRl) and 1-131 (met his aro-116 amyEm+ amyRl) were donated from Y. Ikeda and S. Yuki, respectively. Strain NA64 (metB5 purB6 410

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1975
1975
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…The genotypes would be: amyEm amyRI; amyEm amyR2; amyEn amyRI; amyEn amyR2. Yamaguchi et al (341) have prepared four such strains and studied them in detail. It was found that the a-amylase of isogenic strains carrying amyRI or amyR2 were serologically and biochemically identical regardless of the types of enzyme.…”
Section: A-amylasementioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes would be: amyEm amyRI; amyEm amyR2; amyEn amyRI; amyEn amyR2. Yamaguchi et al (341) have prepared four such strains and studied them in detail. It was found that the a-amylase of isogenic strains carrying amyRI or amyR2 were serologically and biochemically identical regardless of the types of enzyme.…”
Section: A-amylasementioning
confidence: 99%
“…Therefore, the amyR locus could not be part of the amyE gene possibly affecting the specific activity of the enzyme but must, in fact, be a control element dictating the rate of synthesis of the enzyme. Furthermore, amyR was shown to have no effect on the production of either extracellular protease or RNase but was specific for a-amylase (341). The relative location of amyR to amyE has been determined by genetic crosses between amyE mutants with amyRI or amyR2 strains.…”
Section: A-amylasementioning
confidence: 99%
“…amylosacchariticus [1 ], and the a-amylase produced by it is of a different enzymatic type [18,19]. Another possibility is that amyR-n and arnyR-sc, which are closely linked to the structural gene of a-amylase [2,3], are cis-acting controlling regions and while in the chromosome cannot affect the a-amylase gene in the plasmid. On the other hand the high level of transcription and translation of the plasmid-borne c~-amylase gene may already be rate-limiting.…”
Section: Discussionmentioning
confidence: 99%
“…amylosacchariticus. Thus amyR-s, arnyR-n and amyR-sc replace amyR 1, amyR 2 and amyR 3 used previously [2,4]. direction of the construction of the next strain, tf, transformation; NNNG, mutagenization with N-methyl-N-nitroso-N'-nitroguanidine as in [17] and screening for his.…”
Section: Construction Of the Set Of Bacillus Subtilis Hybrid Strainsmentioning
confidence: 99%
See 1 more Smart Citation